Recent advances in platelet processing and storage. (29th January 2016) - Lozano, M.; Cid, J.
Abstract : Platelet rich plasma (PRP) method was the first method used for platelet concentrate (PC) preparation and continues to be the only licensed method in the USA. By contrast in Europe since the eighties of the last century, the PRP method has been progressively replaced by methods based on the removal of the buffy coat (BC) layer. Initially BC were processed individually to produced a single PC but it was soon recognized that the pooling of 4–6 BC units with the addition of a plasma unit of one of the donors of the pool or a platelet additive solution (PAS), improved the efficiency of the separation and eased the transfusion process since the final product was stored as an adult transfusion dose ready to be connected to the patient. Semi‐automatic devices were developed for the separation of whole blood into red blood cells, plasma and the BC and for the separation of the BC into the PC. The introduction of PAS in combination with plasma (in general about 35% of plasma and 65% PAS) for storing PC has shown to offer advantages such as an increased availability of plasma for fractionation, a reduction of transfusion reactions to platelets and a potential reduction in the risk of transfusion related acute lung injury. While early generations of PAS were associated to a decrease in the post‐transfusion corrected platelet count in comparison to PC stored in 100% plasma, this effect has not been found with the newer generation of PAS.